2010
DOI: 10.1095/biolreprod.110.085175
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like 3 Exposure of the Fetal Rat Gubernaculum Modulates Expression of Genes Involved in Neural Pathways1

Abstract: Insulin-like 3 (INSL3) signaling directs fetal gubernacular development and testis descent, but the actions of INSL3 in the gubernaculum are poorly understood. Using microarray gene expression profiling of fetal male rat gubernaculum explants exposed to 10 or 100 nM INSL3, significant changes in expression were identified for approximately 900 genes. Several of the genes showing the largest inductions regulate neuronal development or activity, including Pnoc (34-fold), Nptx2 (9-fold), Nfasc (4-fold), Gfra3 (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 53 publications
(72 reference statements)
4
52
0
1
Order By: Relevance
“…As summarized in Figure 1 As expected, genes involved in the cAMP pathway were identified; mRNA levels of Crem (cAMP-responsive element modulator) and three phosphodiesterases (Pde10a, Pde8a, and Pde4d) were all upregulated following INSL3 exposure [2]. CREM is a transcription factor induced by cAMP, whereas phosphodiesterases are enzymes that degrade cAMP and, thus, regulate intracellular cAMP gradients and responses.…”
Section: Insl3-activated Pathwayssupporting
confidence: 52%
See 2 more Smart Citations
“…As summarized in Figure 1 As expected, genes involved in the cAMP pathway were identified; mRNA levels of Crem (cAMP-responsive element modulator) and three phosphodiesterases (Pde10a, Pde8a, and Pde4d) were all upregulated following INSL3 exposure [2]. CREM is a transcription factor induced by cAMP, whereas phosphodiesterases are enzymes that degrade cAMP and, thus, regulate intracellular cAMP gradients and responses.…”
Section: Insl3-activated Pathwayssupporting
confidence: 52%
“…In addition to the cAMP pathway, Johnson et al successfully identified several genes involved in neurogenesis as well as genes belonging to the bone morphogenetic protein (BMP) and wingless/Int1 (WNT) signaling pathways that were upregulated by INSL3 [2]. Genes involved in neuronal development include Pnoc (codes for the secreted neuropeptide nociceptin) and Pcsk2 (encodes a prohormone convertase that processes prepronociceptin) [2].…”
Section: Insl3-activated Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because no change in Insl3 expression was observed at 13.5 dpc, we surmise that Wnt5a acts either independently or downstream of Insl3 during this process. The latter option is perhaps the most likely, because ex vivo culture experiments on early postnatal rat gubernacula have shown that exogenous INSL3 can induce endogenous Wnt5a expression [57].…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-like 3 protein has been suggested to control testis descent during development ( Johnson et al, 2010). An analysis with murine Sertoli cells and testes has demonstrated that both PNOC mRNA and N/OFQ are induced by FSH.…”
Section: Testismentioning
confidence: 99%